Community music in Oceania : many voices, one horizon - Bartleet, Brydie-Leigh; Cain, Melissa; Tolmie, Diana; Power, Anne (Professor of music education); Shiobara, Mari, 1955- (University of Hawaiʻi Press, 2018)
Community Music in Oceania: Many Voices, One Horizon makes a distinctive contribution to the field of community music through the experiences of its editors and contributors in music education, ethnomusicology, music therapy, and music performance. Covering a wide range of perspectives from Australia, Timor-Leste, New Zealand, Japan, Fiji, China, Taiwan, Malaysia, Singapore, and Korea, the essays raise common themes in terms of the pedagogies and practices used, pointing collectively toward one horizon of approach. Yet, contrasts emerge in the specifics of how community musicians fit within the musical ecosystems of their cultural contexts. Book chapters discuss the maintenance and recontextualization of music traditions, the lingering impact of colonization, the growing demands for professionalization of community music, the implications of government policies, tensions between various ethnic groups within countries, and the role of institutions such as universities across the region. One of the aims of this volume is to produce an intricate and illuminating picture that highlights the diversity of practices, pedagogies, and research currently shaping community music in the Asia Pacific.